2021
DOI: 10.31001/biomedika.v14i1.1128
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity Test of Mycobacterium tuberculosis to Snail Seromucoid and Chitosan in vitro

Abstract: Tuberculosis (TB) is an infection caused by M. tuberculosis (MTb) and is transmitted through droplets of phlegm in the air from patients or those suspected of having TB. In general, treatment for TB is done with anti-tuberculosis drugs (ATDs), specifically streptomycin, isoniazid, rifampicin, and ethambutol (SIRE) that takes a long time due to the level of resistance of MTb bacteria. The resistance of MTb triggers ATDs based on natural bioactive compounds. Chitosan as a result of chitin deacetylation can funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The use of natural ingredients-based galenic preparations has potential as an alternative to ATD therapy. The results showed that the combination of snail seromucoid and chitosan has potential as a bioimmunostimulator and bioimmunodulator in TB therapy (Sutanto et al, 2020;Sutanto et al,2021a;Sutanto et al, 2021b). Durian peel extract polysaccharides and chitosan have the potential to an antimicrobial against MTb isolates (Sutanto et al, 2022).…”
Section: Effectiveness Of Atd Against Mtbmentioning
confidence: 99%
“…The use of natural ingredients-based galenic preparations has potential as an alternative to ATD therapy. The results showed that the combination of snail seromucoid and chitosan has potential as a bioimmunostimulator and bioimmunodulator in TB therapy (Sutanto et al, 2020;Sutanto et al,2021a;Sutanto et al, 2021b). Durian peel extract polysaccharides and chitosan have the potential to an antimicrobial against MTb isolates (Sutanto et al, 2022).…”
Section: Effectiveness Of Atd Against Mtbmentioning
confidence: 99%
“…The results showed that chitosan has multifunctional properties, namely, anti-hypercholesterolemia, antihyperlipidemia, anti-inflammatory, and antimicrobial [11], [12]. The combination of 100% snail seromucoid and 1.5% chitosan with a ratio of 1:2 in vivo is able to accelerate wound healing and has a synergistic effect in vitro as an antimicrobial against Staphylococcus aureus [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis germs have a width of 0.3-0.6 um and a length of 1-4 um. M. tuberculosis does not produce spores and is not motile [13].…”
Section: Introductionmentioning
confidence: 99%